Composing Community: Improvising with Ajay Heble - Lipsitz, George (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2025)
George Lipsitz reflects on Ajay Heble's ongoing legacy. Lipsitz writes, "When I think of Heble’s impact and importance for the study and practice of improvisation I am reminded of the great Duke Ellington’s role in changing music and its contexts of creation, performance, and reception," going on to explore the similarities between Ellington and Heble's roles as musicians, community builders, and public intellectuals.